Mampukah Kalimantan Tengah Mencapai Target Megaproyek Lumbung Pangan Beras Tahun 2023? - Yanuar, Abdul Azis Daffa; Wiyanti, Hana; Ramadhani, Ragil Novia; Permana, Renaldi Ade; Gayatri, Tayasi Ditoresmi; Budiasih, Budiasih (Seminar Nasional Official Statistics, 2023)
Rice is the staple food for the majority of Indonesian people. The availability of rice stocks in Indonesia must be maintained. The government through the food storage megaproject policy which will start in mid-2020 until it is planned to end in 2024 is trying to strengthen national food reserves in several provinces including Central Kalimantan. The study was conducted to confirm whether the total rice production has reached the government's target and to find out what factors influence the amount of rice production and its coefficient values ​​before and after the intervention analysis time period from January 2019 to March 2023. The interrupted time-series and multiple linear regression methods were used in the analysis. The area of ​​paddy harvested land and the price of rice milling are the predictor variables with the consideration that there is a significant effect of the two variables after the intervention. Dummy variables for the time period before and after the intervention were also included to see the effect of the time after the intervention. The results showed that the rice food storage mega project policy had an impact on increasing rice production in Central Kalimantan.